Pengaruh Kepemimpinan Kepala Sekolah Dan Disiplin Kerja Terhadap Kinerja Guru Dengan Efektivitas Sebagai Variabel Pemediasi (Studi Pada Guru SMPN I Torjun Kabupaten Sampang) - Moh. Said Hidayat; Hadi Susanto; Sri Mulyani (Journal of Management and Creative Business, 2023)
The results showed that: 1) Principal leadership had a significant positive effect on teacher performance with an original sample value of 0.011 and a p-value of 0.011. 2) Principal leadership has a significant positive effect on effectiveness with an original sample value of 0.582 and a p-value of 0.000. 3) Work discipline has a significant positive effect on effectiveness with an original sample value of 0.269 and a p-value of 0.024. 4) Work discipline has a significant positive effect on teacher performance with an original sample value of 0.282 and a p-value of 0.005. 5) Effectiveness has a significant positive effect on teacher performance with an original sample value of 0.369 and a p-value of 0.007. 6) Principal leadership has a significant positive effect on teacher performance mediated by effectiveness with an original sample value of 0.215 and a p-value of 0.014. 7) Work discipline has no significant positive effect on teacher performance which is mediated by effectiveness with an original sample value of 0.099 and a p-value of 0.069.